How to construe an atypical bill of lading: The “Luna” and another appeal [2021] 2 SLR 1054 - LOK, Alexis Kaixin (Institutional Knowledge at Singapore Management University, 2023)
Bills of lading have been described as the cornerstone of modern sea carriage (i.e., the transport of goods by sea). Traditionally, a bill of lading serves three functions: (1) it is a receipt by the carrier acknowledging the shipment of goods, (2) it is a memorandum of the terms of the contract of carriage, and (3) it is also a document of title to the goods shipped.